Integrating the Metaverse into the Halal Value Chain: A Maqāṣid-Based Digital Innovation Framework for Global Halal Market Leadership - Yanti, Hani Esa; Sabila, Sasti Amar (Journal of Regional Economics Indonesia, 2026)
This study develops a Metaverse Halal Value Chain (MHVC) framework to integrate metaverse technology into Indonesia’s halal value chain in order to enhance global market competitiveness. Using a qualitative case study approach, data were collected from 25 key informants, including halal entrepreneurs, certification auditors, regulators, academics, and Muslim consumers. Semi-structured interviews, participatory observation, and document analysis were examined through thematic analysis. The findings reveal four key insights: (1) the halal metaverse is perceived as a new spiritual-economic space embedding maqāṣid al-sharīʿah values in digital transactions; (2) digital integration improves certification transparency and cross-sector collaboration; (3) legitimacy and trust remain critical challenges in virtual halal authentication; and (4) Indonesia holds strategic potential to become a global halal ecosystem hub through value-driven digital governance. The proposed MHVC model integrates technological efficiency, collaborative networks, and ethical principles, offering both theoretical advancement and practical guidance for sustainable halal digital transformation.